Pengembangan Sumber Daya Manusia dalam Perspektif epistEmologi Filsafat Islam - Asep Kurniawan (Universitas Islam Negeri Mataram, 2013)
Human beings are the only creature whose capability of knowledge enabling them to develop. However, this could be hampered by the wrong epistemology understanding based on a religion they believe. This research aims to encourage human thought to be dynamically progressive without jeopardizing values of Qur’an. This is carried out through placing the Islamic epistemology on the autonomy of ration and empirical experiences and conducting dialectical process between them and Al-Qur’an. Conclusions derived are that human knowledge can develop dynamically and progressively in line with the spirit of the Qur’an. It automatically has an impact on the development of holistic human resources. In this context, Islamic epistemology then is the main drive for the development of human resources.